Economic burden of hospitalization for Chinese children with chronic kidney disease: a comparison between patients with and without infection - Shi, Xin; Li, Lixia; Zhu, Yuxing; Liu, Xun; Mou, Yikun; Guo, Lei (Frontiers in Pediatrics, 2025)
ObjectiveTo assess hospitalization costs in pediatric chronic kidney disease (CKD) patients, compare the economic burden between those with and without infections, and identify key factors influencing these costs, emphasizing the significant financial impact on families and healthcare systems.MethodsThis retrospective analysis included pediatric patients with CKD hospitalized between May 2011 and April 2020. Clinical characteristics, including demographics, etiology, urinary protein level, estimated glomerular filtration rate, and CKD stage, were analyzed. Hospitalization costs were compared between groups with and without infection using appropriate statistical methods.ResultsAmong 721 pediatric CKD patients included in this study, 388 had primary kidney disease and 333 had secondary kidney disease. Patients in the infection group had significantly higher urine protein levels, longer hospital stays, and higher total hospital fees than those without infection (all P < 0.05). In the primary kidney disease cohort, patients aged 14–18 years incurred the highest costs (16,706 CNY, P = 0.009), while those with 1 + urine protein levels had expenses averaging 29,813 CNY (P = 0.035). In the secondary kidney disease cohort, the 3 + urine protein group had the highest costs (62,841 CNY, P < 0.001). Multiple linear regression identified age, urine protein level, and length of hospital stay as significant cost determinants. Patients with infection in the secondary kidney disease cohort had an average additional expenditure of 13,572.55 CNY compared to those without infection (P = 0.001).ConclusionThis study highlights the economic burden of infection during pediatric CKD hospitalization, emphasizing the need for effective infection management strategies to reduce financial strain and improve outcomes.